Efektivitas ASI Eksklusif Terhadap Tumbuh Kembang Bayi melalui Tes SDIDTK Berbasis Android - Wahyuni Wahyuni; Irmasanti Fajrin (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The future of the country depends on the optimal growth and development of children. About 10% of Indonesia's population are toddlers, and most of them experience growth and development problems. It is important to stimulate, detect and intervene in child development, including exclusive breastfeeding for 6 months. The aim of this study is to examine the effectiveness of exclusive breastfeeding on infant growth and development using the Android-based Stimulation, Early Detection, and Intervention of Child Growth and Development test. The research method utilized is an analytical cross-sectional observational design with 83 respondents purposively selected and conducted from June to August 2023. The data analysis utilized includes the chi-square test, Phi (Φ), and Cramer's V. The instruments included a checklist form, the mobile application for Stimulation, Early Detection, and Intervention of Child Growth and Development version 1.1, a weighing scale, a height measurement tool, and the Maternal and Child Health Book. The research findings indicate that there is no significant relationship between Exclusive Breastfeeding and Infant Growth (p-value = 0.737, phi/Cramer's V = 0.165). However, there is a significant relationship between Exclusive Breastfeeding and Infant Development (p-value = 0.003, phi/Cramer's V = 0.356). It can be concluded that there is no correlation between Exclusive Breastfeeding and infant growth, but there is a relationship with infant development. Therefore, it is recommended to enhance public education regarding the importance of Exclusive Breastfeeding, and further research to understand the relationship between exclusive breastfeeding and infant development, and to apply the findings for targeted intervention programs, particularly utilizing Android-based apps for easier access to information and support for mothers.